Cyanoprokaryota of the coastal solonets of the Kuialnik Estuary (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
At the parched areas of the Kuyalnik Estuary, in alkaline soils covered by communities of true saline vegetation and brackish forb meadows, 42 species of Cyanoprokaryota were revealed by cultures. They belong to 19 genera, 10 families and 4 orders from subclasses Synechococcophycidae (41,5 %), Oscillatoriophycidae (34,1 %) and Nostochophycidae (24,4 %). Characteristic features of the studied habitat are the constant presence and quantitative predominance of cyanoprokaryota in the samples comparing to diatoms and chlorophytes, high number of species per sample, a considerable variety of heterocytous taxa and abundant development of representatives of Nostocales in soil cultures. Ecologically, most of the species are aquatic-subaerophytes known as halophytes (11,9 %), halobionts (40,1 %) and halotolerants (47,6 %). Sites with different plant associations differed in species composition and taxonomic structure of Cyanoprokaryota, which may be associated with varying soil moisture. Identified species analyzed in terms of current views on their taxonomy. New records for Ukraine are Pseudocapsa maritima Komárek, Leptolyngbya norvegica (Gomont) Anagn. et Komбrek, Phormidium litorale Golubić, Ph. viride (Vaucher ex Gomont) Lemmermann, Porphyrosiphon fuscus Gomont ex Frémy, Nodularia crassa (Voronichin) Komárek, Hübel et M. Hübel. The checklist of Cyanoprokaryota of the Kuyalnik estuary based on the original and literature data is given.
Keywords: Cyanoprokaryota, cyanobacteria, hypersaline environments, species diversity, ecology, Kuyalnik estuary.